CAYLEY’S THEOREM FOR DE MORGAN ALGEBRAS - Nurbekyan, L. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
In this paper a Cayley’s theorem is proved for De Morgan algebras. The theorem gives a representation of De Morgan algebras by some class of binary functions.